Analysis of localized bioimpedance from healthy young adults during activities of the vocal folds using Cole-impedance model representation. (July 2021) - Freeborn, Todd J.; Gosa, Memorie
Highlights: Healthy young adult neck bioimpedance well represented by the Cole-impedance model. Cole-impedance parameters of different vocal folds positions not significantly different. Bioimpedance may be alternative technique to assess vocal fold health without phonation. Abstract: The passive electrical properties of a biological tissue, referred to as the tissue bioimpedance, are related to the underlying tissue physiology. These measures have not been explored as a method to assess the health of vocal fold tissues by detecting vocal fold pathologies, which requires exploring differences between healthy and pathological tissues as well as methods to represent and analyze tissue impedances (which motivates this work). Objective: To determine if there are statistically significant differences in Cole-impedance model parameters that represent averaged bioimpedance measurements of localized neck tissues during four vocal folds states (adducted, abducted, voicing /e/, and voicing /ah/). Approach: Tissue bioimpedance was collected from healthy young adults ( N = 10 ) in four vocal fold states with averaged datasets reduced to their Cole-impedance model representations ( R ∞, R 1, C, α ) using a particle swarm optimization approach. Main result: The Cole-impedance model does well represent the collected bioimpedance datasets, but no statistically significant differences in the identified Cole-model parameters of the averaged localized bioimpedance datasets across four vocal folds activities were observed. Significance: Averaged electrical tissue properties may not be sensitive to variations from vocal folds activity. Therefore, localized tissue bioimpedance may be an alternative technique to assess vocal fold tissue health that does not require phonation.